(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article analyzes modern foreign experiences in the landscape development of historical territories. The study explores advanced methods from various countries related to the restoration of historical sites, implementation of green infrastructure, ensuring ecological sustainability, and preservation of cultural heritage. Based on international practices, effective approaches and strategies for landscape development in historical areas are presented. The article also showcases practical examples of landscape architecture, heritage conservation, and community engagement on a global scale. The findings highlight the necessity of applying international experience to create sustainable and ecologically sound landscapes in historical territories.